If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = x + (-22) -16 = x + -22 Reorder the terms: -16 = -22 + x Solving -16 = -22 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -16 + -1x = -22 + x + -1x Combine like terms: x + -1x = 0 -16 + -1x = -22 + 0 -16 + -1x = -22 Add '16' to each side of the equation. -16 + 16 + -1x = -22 + 16 Combine like terms: -16 + 16 = 0 0 + -1x = -22 + 16 -1x = -22 + 16 Combine like terms: -22 + 16 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 4n-5=-17 | | -8(5n+7)=40-8n | | 4x-6+42=90 | | 2[d-(4d+13)+3]=2(d+10) | | 22.5x-15.0=12 | | 2y(6z-x)= | | 48+x=4 | | -5y-5(5z-3y)+3= | | 10p=170 | | 5-(2x+5)=-7 | | 18=0.5 | | -15.5n+17.23+5n=-12.8n-11.06 | | [t+6]=4 | | 3(x+4)-5(2x+3)=-6(x-2)+2(x-6) | | 5-2n=67 | | 64-x=42 | | y-(-6)=2 | | 13x+5x=10 | | 5=17(4x+28) | | 5y=15y+60 | | -13.1+18w=18.2w-10.86 | | 2ab-5ab= | | 1341-4.5x=x | | -11+y=27 | | 2x+12=2x-48 | | 19.9y-9.98=1.29-9.37+20y | | x^2-2ax-3a^2=0 | | -11+38=27 | | 7x+3+8x+6=144 | | -10+8a=6(a-4) | | [2+-3]=-4 | | 54=2x^2+12x |